Avaliação das inter-relações entre função cardiopulmonar e mediadores inflamatórios no diabetes mellitus - Francisco, Cristina de Oliveira (2012)
Diabetes Mellitus (DM) is associated with many complications, including impairment of cardiorespiratory fitness and pulmonary function. Increasing evidences has suggested that comorbidities and systemic inflammation may be involved. The objective of this study was to evaluate cardiorespiratory function in rest and exercise in adults with DM and to verify the relationship between inflammation. Nineteen men with diabetes (51,16 years ± 5,92) and nineteen control subjects (48,79 years ± 7,47) were studied. All individuals were subjected to incremental cardiopulmonary exercise test in cycle ergometer, spirometry, intracellular cytokine lymphocyte profile, lipid and c-reactive protein (CRP) plasma concentration. In the exercise test, maximal overload (W), peak heart rate (HRpeak), oxygen consumption at peak (VO2peak) and at anaerobic threshold (VO2AT), respiratory exchange ratio (RER) were significantly lower in patients with DM than in control subjects. Control subjects and individuals with DM were not different in age, blood pressure, lipid and CRP plasma concentration and intracellular cytokine lymphocites production of TNF-α, IFN-γ, IL-4, IL-10 e IL-17. No significant differences were noted in pulmonary function variables, but abnormalities in these data were predictors to DM. In conclusion, the results confirm impairment of the cardiopulmonary fitness in subjects with DM. The inflammation associated with DM might be influenced by other factors absent in our sample. In addition, the data suggest spirometric abnormalities as predictive to diabetes mellitus.